The Russo-Japanese War in Russian and Japanese Public Opinion and Historical Research - Shendrikova, Diana (Richtmann Publishing, 2012)
This research is aimed to analyze the perception of the Russo-Japanese War of 1904-1905 and its consequences for Russianand Japanese public opinion and research. During the study it proved out that the cultural differences, mutual misunderstandings, andwrong interpretation of each other’s intentions could lead to unresolvable deadlocks, which affect political, economical and culturalrelations. Besides, the interpretations of this conflict by officials and its vision by common people have a great impact on the outcome ofthe war and are also subject of this study. Finally, this research focuses on the territorial issue, which has been dominating the Russo-Japanese relations for centuries and continues to block any attempts of rapprochement on political and in many cases on economicallevels.